2008
DOI: 10.1007/s10725-008-9333-0
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of gene expressions associated with increased allelopathy in rice (Oryza sativa L.) induced by exogenous salicylic acid

Abstract: The defense characteristics of allelopathic rice accession PI312777 and its counterpart Lemont induced by exogenous salicylic acid (SA) to suppress troublesome weed barnyardgrass (BYG) were investigated using the methods of suppression subtractive hybridization (SSH) and real-time fluorescence quantitative PCR (qRT-PCR). The results showed that exogenous SA could induce the allelopathic effect of rice on BYG and this inducible defense was SA doserespondent and treatment time-dependent. PI312777 exhibited highe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 43 publications
(23 citation statements)
references
References 30 publications
0
23
0
Order By: Relevance
“…Allelopathy in crops, however, is considered as a complex phenomenon of chemical ecology, which can be regulated by temperature, illumination, soil condition, herbicides, exogenous hormones and especially nutrient levels in the growth environment (Einhellig 1999;Wu et al 1999;Belz 2007;Shen and Lin 2007;Song et al 2008;Bi et al 2007;Fang et al 2009b;Wang et al 2009). In a previous study, we found that rice cultivar PI 312777 exposed to limited nutrient conditions performed higher allelopathic effect on the accompanying barnyardgrass than that to normal nutrient conditions (Xiong et al 2005;Shen and Lin 2007;Song et al 2008;Wang et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Allelopathy in crops, however, is considered as a complex phenomenon of chemical ecology, which can be regulated by temperature, illumination, soil condition, herbicides, exogenous hormones and especially nutrient levels in the growth environment (Einhellig 1999;Wu et al 1999;Belz 2007;Shen and Lin 2007;Song et al 2008;Bi et al 2007;Fang et al 2009b;Wang et al 2009). In a previous study, we found that rice cultivar PI 312777 exposed to limited nutrient conditions performed higher allelopathic effect on the accompanying barnyardgrass than that to normal nutrient conditions (Xiong et al 2005;Shen and Lin 2007;Song et al 2008;Wang et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…al., 1997;Diaz-Zorita et. al., 2001;Fang et al, 2009;Mohammed & Tarpley, 2009b). In rice, exogenous application of GB or SA increased total antioxidant capacity under high night temperature (Fig.…”
Section: Effects Of Plant Growth Regulators On Plant Antioxidant Enzymentioning
confidence: 92%
“…Suppression subtractive hybridization (Diatchenko et al 1996;Fang et al 2009) was employed to construct a subtractive library. Total RNA was extracted from the shoots of extract-treated achyranthes and its control using the Trizol method (Invitrogen).…”
Section: Establishment Of Subtractive Librarymentioning
confidence: 99%